(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of the solution to the problems of the names of the Kashkadarya river recorded in historical sources. It analyzes and reveals the names of the written sources about the Kashkadarya river from time to time. Brief information is given about the geographical concepts - the names of mountains, rivers, streams, lakes, ditches - which have been recorded in Central Asia since ancient times. However, the written source information about the Kashkadarya River has not been fully analyzed yet.